Regulation of miRNAs as new tool for cutaneous vitality lesions demonstration in ligature marks in deaths by hanging - Neri, Margherita (Sci Rep, 2019)
This study aims to demonstrate that the application of miRNA expression in forensic pathology, in cases of hanging, applying the method on skin samples. The proposed investigative protocol allowed us to highlight a different miRNA expression in the skin ligature marks of subjects who died by hanging compared to healthy skin control samples. The results obtained showed an increase in the expression of miRNAs recognized as regulators of the inflammatory response in skin lesions such as miR125a-5p and miR125b-5p. Furthermore, overexpression of additional miRNAs – miR214a-3p, miR128-3p, miR130a-3p, and miR92a-3p – with anti-inflammatory activity was highlighted. It was possible to document a statistical significance to control skin samples only for miR103a-3p (p < 0.05), miR214-3p and miR92a-3p (p < 0.01) The upregulation of miR222-3p and miR150-5p, respectively related to mast-cell activation and neutrophils after the application of traumatic stimuli supports the immunohistochemical data showed in literature. The diagnostic accuracy of miRNAs could expand the range of diagnostic tools available in the assessment of the vitality of a lesion.